Effect of exercise on depressive symptoms in patients with heart failure - Mahboobeh Maazallahi; Mansoor Arab; Narges Khanjani; Fatemeh Karimi Afshar (Tehran University of Medical Sciences, 2018)
Background & Aim: Depression is common among cardiac patients, especially patients with heart failure and leads to a poor prognosis. This study aimed to assess the effect of exercise on depressive symptoms in patients with heart failure, attending the Cardiac Rehabilitation Center. Methods & Materials: In this clinical trial, 60 patients with NYHA class II and III heart failure who referred to the Cardiac Rehabilitation Center of Shafa Hospital affiliated to Kerman University of Medical Sciences in 2015 were randomly assigned into two groups of 30 patients. Subjects in the intervention group participated in a supervised 8-week exercise program, 3 days per week, while those in the control group only received standard routine care. Data were collected before and after the intervention by the demographic form and the Personal Health Questionnaire Depression Scale (PHQ-8). Data analysis was done by Chi-Square, Wilcoxon, Mann-Whitney U and Nonparametric ANCOVA tests using the SPSS version 21 and R software. Results: The two groups were homogeneous in terms of depression score before the intervention. The median and interquartile range of the score of depression were 10 (5.25) in the control group and 8.5 (9.25) in the intervention group which showed a significant difference (P=0.042). By adjusting the variables of the duration of the disease and the pre-test scores of depression symptoms by non-parametric covariance test, the difference between the two groups was also significant. Conclusion: Exercise can reduce depressive symptoms in patients with heart failure. Clinical trial registry: IRCT201605107844N10